The role of the musical-acoustic thesaurus in the process of orientation in a given space-time - Kalashnyk, Mariya P.; Loshkov, Uriy I.; Yakovlev, Oleksandr V.; Genkin, Anton O.; Savchenko, Hanna S. (Linguistics and Culture Review, 2021)
Musically-acoustic thesaurus is a complex structure which composition of multiple parts is effectuated by multiple channels of receiving information from the outside and ways of manipulation with it. The manipulation is turning of separate facts into systematic knowledge stored in memory. Musically-acoustic thesaurus of collective and individual consists of two groups with duplex connection which are the knowledge of the world as a sonic phenomenon and of human auditory activity and the experience of absorbing the information received, principles of manipulation with it. They fulfill inherent inclination of individual towards usage of auditory images as a requirement for appearance of musical ones. All the sonorities are bracketed in two groups: extra-musical and musical itself. The latter group consists of musical units of acoustically-sonic environment, having utility, practical significance for a person, allowing orientation in given spacetime. At the same time, they are potentially opened to emotional experiences and aesthetic approach towards them. Acoustically-sonic environment possesses basic traits of organization, being reflected in mind by such characteristics as cyclicity, variability, combinationalism, montage structure, simultaneity, interdependency of shape and background.